A Comprehensive Coalition Based Regional Approach to Pediatric Disaster Planning. Issue Volume 34:Issue s1(2019) (May 2019) - Frogel, Michael; Cooper, Arthur; Foltin, George
Abstract : Introduction: Children, who comprise 25% of the US population, are frequently victims of disasters and have special needs during these events. Aim: To prepare NYC for a large-scale pediatric disaster, NYCPDC has worked with an increasing number of providers that initially included a small number of hospitals and agencies. Through a cooperative team approach, stakeholders now include public health, emergency management, and emergency medical services, 28 hospitals, community-based providers, and the Medical Reserve Corps. Methods: The NYCPDC utilized an inclusive iterative process model whereby a desired plan was achieved by stakeholders reviewing the literature and current practice through discussion and consensus building. NYCPDC used this model in developing a comprehensive regional pediatric disaster plan. Results: The Plan included disaster scene triage (adapted for pediatric use) to transport (with prioritization) to surge and evacuation. Additionally, site-specific plans utilizing Guidelines and Templates now include Pediatric Long-Term Care Facilities, Hospital Pediatric Departments, Pediatric and Ob/Newborn/Neonatal Intensive Care Services and Outpatient/Urgent Care Centers. A force multiplier course in critical care for non-intensivists is provided. An extensive Pediatric Exercise program has been used to develop, operationalize and revise plans based on lessons learned. This includes pediatric tabletop, functional and full-scale exercises at individual hospitals leading to citywide exercises at 13 and subsequently all 28 hospitals caring for children. Discussion: The NYCPDC has comprehensively planned for the special needs of children during disasters utilizing a pediatric coalition based regional approach that matches pediatric resources to needs to provide best outcomes. The NYCPDC has responded to real-time events (H1N1, Haiti Earthquake, Superstorm Sandy, Ebola), and participated in local (NYC boroughs and executive leadership) and nationwide coalitions (National Pediatric Disaster Coalition). The NYCPDC has had the opportunity to present their Pediatric Disaster Planning and Response efforts at local, national and International conferences.